2021
DOI: 10.1590/1678-4324-2021200639
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Partial Purification and Characterization of Bromelain from Pineapple (Ananas Comosus) Crown, Core and Peel Waste

Abstract: Ananas Comosus (also known as pineapple) is a part of Bromeliaceae family and it is consumed as food as well as folk medicine for the treatment of various diseases. It is reported that pineapple is a rich source of bromelain, a cysteine protease and it is considered as an important enzyme in different industries due to its significant therapeutic and industrial applications such as anticancer, anti-inflammatory and meat tenderizing. Bromelain is mostly present in fruit and stem of pineapple, but it is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…As for the pH effect on the activity of bromelain from various pineapple parts, our results are consistent with the observations of Gul and coworkers [33], although other studies highlighted a relevant decrease of the proteolytic activity of fruit bromelain on sodium caseinate at pH higher than 8 [19,29]. This behavior may be explained by differences in terms of bromelain source and of variety, harvesting, and ripening stage of the pineapples used in the various studies [17].…”
Section: Enzymatic Kinetic Measurementssupporting
confidence: 91%
“…As for the pH effect on the activity of bromelain from various pineapple parts, our results are consistent with the observations of Gul and coworkers [33], although other studies highlighted a relevant decrease of the proteolytic activity of fruit bromelain on sodium caseinate at pH higher than 8 [19,29]. This behavior may be explained by differences in terms of bromelain source and of variety, harvesting, and ripening stage of the pineapples used in the various studies [17].…”
Section: Enzymatic Kinetic Measurementssupporting
confidence: 91%
“…The purification fold of 1.56 along with 78.84% yield was obtained with 50% ammonium sulfate fractionation, which is in agreement with Sharma & Vaidya (2018). Gul et al (2021) also reported the highest purity and yield percentage of pineapple crow bromelain, precipitated at 50% concentration. The activation of enzyme during ammonium sulfate precipitation, and removal of interfering substances during centrifugation under cool condition might have contributed to higher purity and activity recovery also.…”
Section: Purification Profilementioning
confidence: 89%
“…Hence, ultrafiltration technique was conducted to completely remove ammonium sulfate salt and purify the bromelain to increase the purity of the enzyme. The effectiveness of the centrifugal ultrafiltration method was indicated by increasing purification fold and bromelain yield, equivalent to that in the study conducted by Gul et al (2021). The yield is the amount of enzyme activity preserved in the purified sample compared with the original sample, the crude.…”
Section: Purification Yield and Enzymatic Activitymentioning
confidence: 91%
“…Principally, ammonium sulfate salt will increase the surface tension of the water and enhance the hydrophobic interaction between the target protein and water, causing salting out (Setiasih et al, 2019). 50% ammonium sulfate concentration was chosen based on the research done by Gul et al (2021), which found that 50% concentration had the highest recovery of bromelain (215.22%). However, without an appropriate technique for the desalting process, excess ammonium salt in the extract solution would interfere with the protein binding mechanism, thus underestimating the true value of the assays performed, especially colorimetric assays.…”
Section: Bromelain Purificationmentioning
confidence: 99%